MINERALIZATION OF BACTERIAL SURFACES - Schultze-Lam S.; Fortin D.; Davis B.S.; Beveridge T.J. (My University, 1996)
Bacteria are very small (~ 1.5 μm3), but have the largest surface area to volume ratio of any life form. As a result, by providing interfaces for sorption of metal cations, bacteria are efficient scavengers of dilute metals and can concentrate them from the surrounding aqueous environment. This is mainly due to the overall anionic charge of bacterial surfaces imparted by the macromolecules which make up their fabric. Once metal ions have interacted with the electronegative sites on these molecules, they nucleate the formation of fine-grained minerals using anions from the external milieu as counter-ions for additional metal complexation. It is not unusual for bacteria to precipitate an amount of metal equal to, or exceeding, their cellular weight. Diverse mineral types, including hydroxides /oxides, carbonates, sulfates/ sulfides, and phosphates are common and can be in. amorphous or crystalline phases depending on the stage of mineral development. Since bacteria are ubiquitous in the natural environment, they can potentially play a significant role in the development of fine-grain minerals in soils and sediments. It is also possible that their capacity for metal immobilization can be used to counteract the disastrous effects of acid mine leachates.
Keywords: MINERALIZATION; BACTERIAL SURFACES; METAL IMMOBILIZATION; SCAVENGING DILUTE METALS